2021
DOI: 10.3390/ijerph182111556
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fiber Intake and Risk of Pancreatic Cancer: Systematic Review and Meta-Analysis of Observational Studies

Abstract: The burden of pancreatic cancer varies greatly across countries, with the number of deaths, incident cases, and disability-adjusted life years more than doubling in recent years, and with high-income countries having the highest incidence and mortality rates. We conducted this systematic review with meta-analysis with the goal of summarizing the current evidence on dietary fiber intake and its role in reducing the risk of pancreatic cancer, given the importance of identifying risk factors. This systematic revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 65 publications
(165 reference statements)
0
30
0
Order By: Relevance
“…Third, the sources of dietary fiber (e.g., fruit, vegetables, legumes and cereals) were not available and thus we were unable to perform stratified analyses according to fiber sources. Fourth, previous studies have suggested that dietary fiber intake reduced the risk of pancreatic cancer, colon cancer, and rectal cancer [ 44 46 ]. Unfortunately, we were unable to perform analyses according to the specific causes of cancer death or cardiovascular death as relevant data were not available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the sources of dietary fiber (e.g., fruit, vegetables, legumes and cereals) were not available and thus we were unable to perform stratified analyses according to fiber sources. Fourth, previous studies have suggested that dietary fiber intake reduced the risk of pancreatic cancer, colon cancer, and rectal cancer [ 44 46 ]. Unfortunately, we were unable to perform analyses according to the specific causes of cancer death or cardiovascular death as relevant data were not available.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the sources of dietary fiber (e.g., fruit, vegetables, legumes and cereals) were not available and thus we Table 4 Association between dietary fiber intake and cancer mortality * Adjusted for age (continuous), sex (male vs. female), race (non-Hispanic White vs. Other), body mass index (BMI, < 25.0 kg/m 2 vs. ≥ 25.0 kg/m 2 ), education (≤ high school vs. ≥ some college), smoking status (never vs. former ≤ 15 years since quit vs. former > 15 years since quit vs. former year since quit unknown vs. current smoker ≤ 1 pack per day vs. current smoker > 1 pack per day vs. current smoker intensity unknown), marital status (married vs. not married), alcohol drinking status (never vs. former vs. current), and total energy intake (continuous) were unable to perform stratified analyses according to fiber sources. Fourth, previous studies have suggested that dietary fiber intake reduced the risk of pancreatic cancer, colon cancer, and rectal cancer [44][45][46]. Unfortunately, we were unable to perform analyses according to the specific causes of cancer death or cardiovascular death as relevant data were not available.…”
Section: Variablesmentioning
confidence: 93%
“…In this sense, it is also worth noting that in the second meta-analysis, case-control studies drove the overall epidemiological link with the decreased risk of PC, whereas association in cohort studies was weaker. People on healthy/prudent diets tend to eat more vegetables, fruits, fiber, and other compounds with lower risk for PC in epidemiological studies [ 10 ]; in this sense, case-control studies are more likely to have longer follow-up periods (compared to cohort studies) in which the effect of exposure to healthy dietary components may be increased [ 10 ], and this is likely to explain the higher robustness found in our analysis. More in general, design-attributable differences in the epidemiologic study of cancer etiology have been deeply investigated, and case-control and cohort studies have complementary roles in cancer epidemiology, also considering their advantages and limitations [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years several studies have been published, and new evidence has emerged on the possible role of diet and its components in the prevention of PC [ 10 , 11 , 12 , 13 ]. There is, therefore, a need to analyze this important body of evidence.…”
Section: Introductionmentioning
confidence: 99%
“…For example, dietary fiber, one of the important nutrients in foods, has many benefits in preventing diseases. Dietary fiber intake can decrease the risk of cancers by diluting carcinogens, disrupting the gut microbiota, and modulating insulin sensitivity and obesity [ 94 , 95 ]. Vitamin C is a powerful antioxidant.…”
Section: Bioactive Compounds and Their Anticancer Functionsmentioning
confidence: 99%